2016
DOI: 10.1177/1538192716653504
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Dietary Patterns and Health Status of Diabetes Among At-Risk Latino College Students

Abstract: This study examined within-group differences in obesity-related dietary behaviors and the health status of 156 Latino students at-risk for diabetes due to family history. Approximately 58% of students were overweight/obese, with female students reporting a greater risk for diabetes. Consumption of meats, fried potatoes, breads, and tortillas was associated with higher BMI and diabetes risk indices. Differences in dietary behaviors were found based on students’ college profile and sociodemographic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
(139 reference statements)
1
1
0
2
Order By: Relevance
“…In the current study, high consumption of foods high in saturated fats is associated with excess body weight. These results are in line with the findings of a study in university students in which the consumption of high-fat foods was associated with a poorer health status according to BMI scores ( 48 ). In addition, it is important to mention that the type of fat influences obesity.…”
Section: Influence Of Saturated Fats Intakesupporting
confidence: 91%
“…In the current study, high consumption of foods high in saturated fats is associated with excess body weight. These results are in line with the findings of a study in university students in which the consumption of high-fat foods was associated with a poorer health status according to BMI scores ( 48 ). In addition, it is important to mention that the type of fat influences obesity.…”
Section: Influence Of Saturated Fats Intakesupporting
confidence: 91%
“…In particular, college aged students face an important challenge: with increased independence, limited budget and spare time, healthful food choices are hard to make (Sogari et al, 2018;Sprake et al, 2018). College environment and lifestyle in Latin America include late snacking, skipping meals, fast food and alcohol intake during social events which explain why it has been repeatedly shown that there is an important weight gain during the first year of college, and this weight (which includes a fat percentage increase) is maintained throughout the whole university period (Huang et al, 2003;Lacaille et al, 2011;Santos et al, 2017). In fact, epidemiological studies have shown that the greatest weight and fat mass gain happen between 18 and 29 years of age, which include college years (Santos et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Los alimentos que destacan por su asociación con ecnt cuando se consumen en exceso son las carnes rojas, las carnes procesadas y los huevos, ya que se ha visto que quienes los consumen de manera habitual incrementan en un 200% el riesgo de hipertensión que quienes no los consumen (Schwingshackl et al, 2017a). Estos alimentos mostraron resultados similares en la asociación con el desarrollo de diabetes (Schwingshackl et al, 2017b) y obesidad; en este último padecimiento se incluyen también los alimentos realizados con cereales refinados (Schlesinger et al, 2019), los cuales en el contexto latinoamericano se encuentran presentes en la dieta a través de pan blanco, tortillas, harinas con las que se elaboran galletas y pasteles, papas fritas industriales, entre otros (Santos et al, 2017).…”
Section: Alimentos Relacionados Con El Desarrollo De Obesidad Diabete...unclassified